OPTIMIZING THE ROLE OF ISLAMIC EDUCATION TEACHERS IN 21ST CENTURY LEARNING - dalila Khoirin (Jurnal Ilmiah Pesantren, 2021)
This study aims to optimize the competence of Islamic religious education teachers so that students can master the skills needed in the 21st century, namely critical thinking skills in solving problems,communicating, collaborating and leadership as well as being creative and innovative. In mastering these skills, there must be optimization of PAI teacher competencies, namely pedagogic, social, personality, professional and leadership. Qualitative approaches and types of literature research are used in this study, therefore, the data sources are taken from books, articles, journals and other documents. Research data were collected using documentation techniques, then analyzed by reading, understanding, examining, connecting and concluding. From this research, it can be seen that by optimizing the five competencies of Islamic Education teachers, the student skills needed in the 21st century will be easily achieved.